'It showed me that I was not dumb' the role of flexible learning programmes in enabling cognitive (re)-engagement. Issue 8 (2nd July 2020) - Thomas, Jeffrey; Dyment, Janet; Hay, Ian
ABSTRACT: This study investigates the change in students' cognitive engagement as a result of participation in a Flexible Learning Programme. Using an understanding of engagement as both a process and a relationship between the students and their school, we sought to determine whether students' perception of competency, willingness to engage, and establishment of learning goals were different after the programme compared with before enrolment. To achieve this, we used a range of data sources which included both student and teacher voice, collected prior, during and after the programme. Data from the programme's complete cohort of 46 students collected over a span of five years were analysed. Findings revealed that students' cognitive engagement increased within the programme, and these improvements were significantly maintained after students returned to their mainstream 'host' school. These findings provide a response to some common criticisms of Flexible Learning Programmes and add to the body of evidence supporting their role in the reengagement of disengaged students.